RISK ANALYSIS IN DEVELOPING HORIZONTAL TO VERTICAL HOUSING USING SEVERITY INDEX METHOD (CASE STUDY: RUMAH SUSUN PALDAM, BANDUNG) - Almira, A; Anjastari, H A; Gaol, D KL; Zuna, H T; Wahyudi, A R (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
Currently the gap between the demands with the supply of livable homes is relatively large. From various national figures, it is noted that this challenge requires a structured, systematic and massive handling / management effort, with no exception in the Capital of West Java Province, Bandung City. To fulfill the community’s need for housing, the government has financial constraints due to the limited State Budget, so the government needs the help from business entities to meet the housing needs, as know as PPP. In this case, the construction is on land that is inhabited by the retired TNI community, so it is a separate and risky challenge. In general, any infrastructure development has a risk that needs to be mitigated. Therefore, it is necessary to carry out further and in-depth studies on what risks are affected and the allocation of risks so that management can be prepared. This paper aims to determine the risks posed in the construction of the Paldam Flats in Bandung. The analytical method used is the Severity Index Method. The analysis phase is carried out by starting with a preliminary survey of the parties concerned, then identifying risks. From the main survey results, this data will be processed with a risk probability matrix and risk impact, so it can be seen that the variables are included in the high category. From the results of data analysis, the risk that gives the greatest influence is the increase in construction costs and commercial revenues.